Incorporating the visibility of coastal energy infrastructure into multi-criteria siting decisions. (December 2015) - Griffin, Robert; Chaumont, Nicolas; Denu, Douglas; Guerry, Anne; Kim, Choong-Ki; Ruckelshaus, Mary
Abstract: Concern about the visibility of large infrastructure development often drives public opposition to these projects. However, insufficient analytical tools to assess visibility across a large number of alternate sites prior to siting typically results in the omission of visibility in multi-criteria siting processes, leading to inferior site selection and often costly litigation. This paper presents an approach for deriving visibility maps based on the location and duration of viewing by residents and visitors and demonstrates its use in illuminating tradeoffs by comparing these maps to wind energy value maps in the context of offshore wind energy development in the Northeastern United States. Highlights: A method to include visibility concerns into infrastructure siting is proposed. The approach allows for consideration of visibility prior to siting decisions. The method estimates visibility based on the landscape distribution of viewers. Resulting maps can be compared to other siting criteria for optimal siting. It is demonstrated in the context of siting the first offshore U.S. wind farm.